The Familial Risk of Endometriosis among the Female Relatives of Patients with Endometriosis in Greece. Issue 3 (July 2017) - Matalliotakis, Michail; Goulielmos, George N.; Zervou, Maria I.; Matalliotaki, Charoula; Koumantakis, Georgios; Matalliotakis, loannis
Introduction: Endometriosis is a gynecologic disease affecting up to 10% of the women and a major cause of pain and infertility. It is a complex genetic disease with an overall heritability estimated at around 4%. We aimed to study the familial risk of endometriosis among the female relatives of patients with endometriosis. Furthermore, we compared the demographic variable characteristics of patients with and without family history of endometriosis. Methods: We evaluated the medical reports of 400 women with endometriosis and 400 without, all of whom underwent consultation for infertility or pelvic pain and had surgery between 2002 and 2016. This retrospective study was conducted in the Obstetrics and Gynecology Department of Venizeleio General Hospital of Heraklion, Crete. Data were collected from patients' charts and analyzed by statistical methods including x 2 and Mann-Whitney U test. Results: The overall risk of first-degree relatives of endometriosis was 10.2% versus only 0.7% of controls p<0.001. Among 25 pairs of sisters we found one or more sisters with endometriosis. Additionally, we reported a family with six members with endometriosis within three generations. In women with positive family history of endometriosis we observed earlier menarche and more severe stage of endometriosis. Moreover, we did not notice any difference in the demographic characteristics between the endometriosis and the control group patients; similar clinical data was observed in both groups. Conclusions: These data support the view that genetic factors play a role in the development of this condition.